GREAT SILK ROAD LEGENDS AND MYTHS: “FORTY LEGENDARY GIRL” - Beskempirova A. U.; Baltabayeva А. Yu.; Yildiz Naciye (Scientific Journal of Pedagogy and Economics, 2019)
The article deals with the importance of studying the immortal legendary prose examples of legendary stories about the monuments onthe adjacent territories of Turkestan regionalong Great Silk Road. Looking at mythical stories within this legendary prose, it is thought of how ancient the human consciousness, the degree of thinking, the way of life were. As world myths become the main topic of scientific research and are comparable to historical comparisons, myths also have different levels of social development, historical levels, types and thematic areas. One of such models is compared to several versions of the legend about “Forty Girls” in Kazakh, Uzbek and Kyrgyz folklore. This article discusses the tragic fate of the forty girls and the smell of the national consciousness, the high spirit in the hearts of girls who wanted to remain in their own country instead of living the in the hands of enemy. Forty Girls monument – an old natural mountain hills wherenature has long been regarded as a sacred monument. There are many similarities in variants of thislegendamong Turkic peoples. Everywhere it is said that the tragic fate of forty girls and the end of the legend are similar. In any country, the stone sculpture “Forty Girl” has become a great place for travelers. Locals treasure and sanctify this holy place.